Seroprevalence of hepatitis E virus infection in pregnant women: a systematic review and meta-analysis - Ahmad, Tauseef; Hui, Jin; Musa, Taha Hussain; Behzadifar, Masoud; Baig, Mukhtiar (Annals of Saudi medicine, 2020)
Hepatitis E virus (HEV) infection has emerged as a global public health problem that affects millions of people every year. Systematically review data on the prevalence of HEV IgG antibody among pregnant women around the world. Potentially relevant studies were identified by a search of PubMed and ScienceDirect, and by a manual search of the reference lists of identified studies. Observational studies in English with no age or area restriction. Reviews, duplicate, book chapters, and other irrelevant studies were excluded. Independent searching by two investigators (TA, THM). In the 6137 retrieved studies, 15 studies met the inclusion criteria. The studies included 7160 pregnant subjects from 11 countries. Most studies were from Africa. Of the 7160 subjects, 1182 were positive to anti-HEV IgG antibody, and only 66 were anti-HEV IgM antibody positive. The highest seroprevalence of anti-HEV IgG antibody (61.29%) was reported in Sudan and the lowest (3.41%) was reported in Italy. The overall pooled prevalence was 16.51% (95% CI: 0.10-0.23). The heterogeneity level was I = 98%; P≤.01. The seroprevalence of anti-HEV IgG antibody among pregnant women differs by geographic location. Further studies are recommended to evaluate incidence, morbidity, and mortality in those areas where the disease is prevalent. Seroprevalence was only determined for the anti-HEV IgG antibody, which mostly indicates past infection. Heterogeneity was high among the studies in the analysis. None.